Divine Ratios : Poems - Osherow, Jacqueline (Book collections on Project MUSE., 2023)
"The cities in Jacqueline Osherow's new collection of poems, Divine Ratios, include a Berlin still overwhelmed by guilt for World War II; a Shanghai where a taxi driver teaches his American passengers to recite a Tang Dynasty poem in Chinese; a Baltimore devastated by police violence, where women in a laundromat take in and guide a stranger; as well as Urbino, the quintessential ideal city of the Italian Renaissance. The book also visits natural wonders: the shapeshifting hoodoos of Utah's Bryce Canyon, the lupines and sandhill cranes of southwestern Montana, the coyotes adapting to life in New York City. Osherow's poems find their bearings through contrast, as a breezy conversational tone provides a counterpoint to traditional formal verse. Divine Ratios shows a distinguished American poet navigating spaces and forms with enrapturing insight, craft, and humanity"--